Design of an F1 hybrid breeding strategy for ryegrasses based on selection of self-incompatibility locus-specific alleles - Pembleton, Luke; Shinozuka, Hiroshi; Wang, Junping; Spangenberg, German; Forster, John W.; Cogan, Noel (Frontiers in Plant Science, 2015)
Relatively modest levels of genetic gain have been achieved in conventional ryegrass breeding when compared to cereal crops such as maize, current estimates indicating an annual improvement of 0.25-0.6% in dry matter production. This property is partially due to an inability to effectively exploit heterosis through the formation of F1 hybrids. Controlled crossing of ryegrass lines from geographically distant origins has demonstrated the occurrence of heterosis, which can result in increases of dry matter production in the order of 25%. Although capture of hybrid vigour offers obvious advantages for ryegrass cultivar production, to date there have been no effective and commercially suitable methods for obtaining high proportions of F1 hybrid seed. Continued advances in fine-scale genetic and physical mapping of the gametophytic self-incompatibility (SI) loci (S and Z) of ryegrasses are likely in the near future to permit the identification of closely linked genetic markers that define locus-specific haplotypes, allowing prediction of allelic variants and hence compatibility between different plant genotypes. Given the availability of such information, a strategy for efficient generation of ryegrass cultivars with a high proportion of F1 hybrid individuals has been simulated, which is suitable for commercial implementation. Through development of two parental pools with restricted diversity at the SI loci, relative crossing compatibility between pools is increased. Based on simulation of various levels of SI allele diversity restriction, the most effective scheme will generate 83.33% F1 hybrids. Results from the study, including the impact of varying flowering time, are discussed along with a proposed breeding design for commercial application.